Evaluating Endoscopic Ipsilateral Endonasal Corridor Approaches to the Anterolateral Wall of the Maxillary Sinus: A Computerized Tomography Study - Vatcharayothin,Navarat (2022)
Abstract Introduction The endoscopic access to lesions in the anterolateral wall of the maxillary sinus is a challenging issue; therefore, the evaluation of access should be performed. Objective To assess the accessibility of three endoscopic ipsilateral endonasal corridors. Methods Three corridors were created in each of the 30 maxillary sinuses from 19 head cadavers. Accessing the anterolateral wall of the maxillary sinus was documented with a straight stereotactic navigator probe at the level of the nasal floor and of the axilla of the inferior turbinate. Results At level of the nasal floor, the prelacrimal approach, the modified endoscopic Denker approach, and the endoscopic Denker approach allowed mean radial access to the anterolateral maxillary sinus wall of 42.6 ± 7.3 (95% confidence interval [CI]: 39.9-45.3), 56.0 ± 6.1 (95%CI: 53.7-58.3), and 60.1 ± 6.2 (95%CI: 57.8-62.4), respectively. Furthermore, these approaches provided more lateral access to the maxillary sinus at the level of the axilla of the inferior turbinate, with mean radial access of 45.8 ± 6.9 (95%CI: 43.3-48.4) for the prelacrimal approach, 59.8 ± 4.7 (95% CI:58.1--61.6) for the modified endoscopic Denker approach, and 63.6 ± 5.5 (95%CI: 61.6-65.7) for the endoscopic Denker approach. The mean radial access in each corridor, either at the level of the nasal floor or the axilla of the inferior turbinate, showed a statistically significant difference in all comparison approaches (p < 0.05). Conclusions The prelacrimal approach provided a narrow radial access, which allows access to anteromedial lesions of the maxillary sinus, whereas the modified endoscopic Denker and the endoscopic Denker approaches provided more lateral radial access and improved operational feasibility on far anterolateral maxillary sinus lesions.